PERAMALAN NILAI EKSPOR DI PROVINSI BANTEN TAHUN 2024 PADA KATEGORI NON MIGAS MENGGUNAKAN METODE ARIMA - Maulani, Nenden Gustika; Huda, Miftahul; Sukmawati, Sri (Universitas Bina Bangsa, 2024)
Non-Oil and Gas Exports play an important role in Indonesia's economy, including in Banten Province. This is due to the significant contribution of non-oil and gas exports to the country's foreign exchange earnings. The fluctuations in demand for non-oil and gas exports in the international market can be used as a forecasting basis to determine the balance between production and demand for non-oil and gas products in the international market. The aim of this research is to obtain forecasts of non-oil and gas export values from April to December 2024. The data used in this study is monthly time-series data of non-oil and gas export values from January 2020 to March 2024. The forecasting method used is the Box-Jenkins ARIMA (p, d, q) model. The forecasting results produced the best model, ARIMA (4,2,0), with the equation is with an MSE value is 11,581.7. Non-oil and gas exports in 2024 showed fluctuations from April to December 2024, with each forecasted value as follows: April at 1,033.94, May at 1,025.74, June at 1,075.72, July at 1,069.83. August at 1.113,51, September at 1059,30, October at 1.113,33, November at 1.133,85, and December at 1120,29